PERILAKU MACAN DAHAN KALIMANTAN (Neofelis diardi borneensis) DI KANDANG TRANSIT BALAI KONSERVASI SUMBER DAYA ALAM KALIMANTAN SELATAN - Alfian Alfian; Anni Nurliani; Titik Sundari (Universitas Lambung Mangkurat, 2024)
In a broad sense, behavior is the visible actions carried out by living creatures to adapt to environmental conditions for survival. N. diardi borneensis is one of the endemic animals of Kalimantan and is considered the highest leader of the food chain in Kalimantan. The Bornean clouded leopard was once considered the same species as the clouded leopard (Neofelis nebulosa), but in 2006 it was classified as a different species. The Bornean clouded leopard, which is endangered, is very interesting as an object of observation. The presence of the Bornean clouded leopard in the South Kalimantan (Kalsel) BKSDA transit cage after evacuation is an opportunity to observe the behavior of this rare animal. This study aims to determine the behavior of N. diardi borneensis while in the South Kalimantan BKSDA transit cage as scientific information that can be used as a reference for preservation and conservation programs. The method used is observation using the focal animal sampling method. Observations are divided into three periods: in the morning from 08.00 – 09.00, in the afternoon from 12.00 – 13.00, and the afternoon from 16.00 – 17.00. In each period, observations were made for 1 hour with recording intervals, namely every 5-minute interval, to calculate the duration/time of the behavior and then calculate the percentage. The results obtained from observing the behavior of N. diardi borneensis for 14 days are the behavior shown by N. diardi borneensis during the transit drum, namely resting behavior with an average duration of 1883 minutes (75%), movement behavior with an average duration of 584 minutes (23%), and eating behavior with an average duration of 53 minutes (2%). The Bornean clouded leopard has a unique special behavior: spending most of its time doing activities on tree branches (arboreal).